Gas and methane production vis-à-vis loss of energy as methane from in vitro fermentation of dry and green forages in sheep and goat inoculums - SINGH, SULTAN; KUSHWAHA, B P; ANELE, U Y; NAG, S K; MISRA, A K; SINGH, ARPANA (The Indian Journal of Animal Sciences, 2020)
Gas production, methane and energy loss from 10 dry and 12 green fodders were evaluated in vitro using sheep and goat inocula. Dry matter intake and digestible DM (DDM) were higher for green (2.45% and 62.28%) than dry fodders (1.72% and 52.88%), respectively. Mean in vitro dry matter digestibility was higher for green than dry fodders in rumen inocula of sheep (63.51 vs 45.34%) and goat (61.36 vs 41.36%), respectively. After 12 h, gas production was higher for green than dry fodders in sheep (69.70 mL/g vs 64.40) and goat inocula (61.73 vs 55.53 mL/g). Gas production was higher for dry and green fodders in sheep inoculums vs goat at 12, 24 and 48 h. At 12 h, methane production was higher for green than dry fodders both in sheep (12.96 vs 9.69 mL/g) and goat (13.34 vs 9.14 mL/g). Total CH4 production was higher for green than dry fodders with both sheep (40.92 vs 33.83 mL/g) and goat inocula (33.34 vs 30.47 mL/g), respectively. Methane production was higher from fermentation of green fodders than dry fodders in rumen inocula from goat (19.27 vs 14.16) and sheep (18.57 vs 14.76 g/kg DM), respectively. Green fodders produced higher CH4 with goat (33.75 g/kg DDM) vs sheep inocula (29.65 g/kg DDM). Methane production (g/kg DDM) and energy loss as methane (CH4 % GE) was similar for dry and green fodders fermented in sheep and goat inocula. Overall, results showed that green forages produced more CH4 compared with dry forages so this piece of information should be put into consideration for sustainable and environmentally friendly production system.